The effect of leaching agents on the growth and uptake of rare earth elements and uranium by Dicranopteris linearis - Naily Asna, Muna; Nur Nazifa Nasuha, Muhammad; Mohd Yusri, Mohd Yunus; Karimah, Kassim; Nurul ‘Ain, Jamion; Jalina, Kassim; Hezlin Aryani, Abdul Rahman; Yong, Soon Kong (Malaysian Society of Soil Science, 2024)
Commercial extraction of rare earth elements (REE) from ion adsorption clay (IAC) may release toxic elements and radionuclides and pollute the environment. Dicranopteris linearis is a fern species available in Malaysia and can accumulate REE and uranium (U) with greater efficiency, especially when IAC is treated with a leaching agent such as hydrolyzed humic acid (FA). This study aims to investigate the growth of D. linearis and its uptake for REE and U in an IAC treated with FA produced at pH 1 (1 % w/w FA pH 1) and pH 6 (1 % w/w FA pH 6). The results were compared with those of commercial ammonium sulfate (0.45 M (NH4)2SO4), and artificial rain (10 mM CaCl2). The REE and U content were analyzed using inductively coupled plasma-optical emission spectrometry (ICP-OES). The t-test showed a significance value (p<0.05), indicating that the difference between the REE and U uptake of D. linearis with different treatments are significant. The highest Bioconcentration Factor (BCF) and Translocation Factor (TF) values for scandium (Sc) (5.29±0) were recorded when IAC was treated with FA pH 1. Treatment of IAC with FA pH 6 also allows translocation of cerium (Ce) to the shoot of D. linearis (TF= 1.96±0). A significantly higher uptake for praseodymium (Pr) and U was observed when IAC was treated with (NH4)2SO4, possibly due to a greater mobilization that allows more uptake at the shoot of D. linearis. Using FA pH 6 may offer a safer alternative to (NH4)2SO4 for selectively extracting Ce and lanthanum (La).